A comparative finite element study of stress and deformation on three commonly used all ceramic fixed denture prosthesis under the influence of different bite forces - Raghavan, Rohit; S Raj, Jency; M Kunjappan, Shiji; Christopher, Kiran; Kambiranda, Sapna C (International Journal of Dental Research, 2017)
Aim: To simplify the complexity in design, modeling and analysis of Fixed Partial Dentures (FPD) and to evaluate the maximum stress and deformation developed using Finite-Element Method.Materials and Methods: The specimen was created based on monoblock concept. The monoblock concept assumes that the total FPD unit, i.e., Abutment, pontic, connector and retainer together will act as a single unit. Monoblock castings do not differ from those made in segments and later welded as regard to the distribution of stresses. The Specimen of dimension 30 X 5 X 5mm were made of the three commonly used FPD materials such as feldspathic ceramics, Lithium di silicate and Zirconia. Rectangle shape was considered with notches at 1 X 450 as a close approximation of actual FPDs. The modeling was done using Solid Works 2012, and analysis was carried out using ANSYS Mechanical APDL R14.5. The maximum stress and deformations corresponding to various masticatory loads (100 N, 500 N, 600N, 800 N & 1000 N) were found out, and the results were compared with previous studies in FPD.Results: The results revealed that the maximum principal stress and deformation are found at the centre of the pontic. Furthermore, it was found that for all masticatory loads, the maximum stress and deformation were encountered in Feldspathic ceramic and least for Zirconia.Conclusion: A less complex model using the monoblock concept was developed to design and analyze FPD, so that the meshing complexities, computational time and cost can be reduced drastically. The results could well be considered as a benchmark in FPD-related studies.